(untitled) (Research, Society and Development, 2020)
The objective of this study is to describe the epidemiological profile of reported cases of gestational syphilis in the State of Amapá in the five-year period from 2014 to 2018 and to associate the sociodemographic and clinical variables found in the research, and to evaluate the spatio-temporal distribution of the disease in the counties through data plotted on maps using the SIG. Retrospective cross-sectional epidemiological study, with a quantitative nature and descriptive approach. Dice on syphilis notifications in pregnant women were taken from the Notifiable Diseases Information System (SINAN) and the number of born alive from the Alive Born Information System (SINASC), and the geographic meshes of the Brazilian Institute of Geography and Statistics (IBGE). From 2014 to 2018, 986 cases of syphilis were registered in pregnant women, with a number bigger in the City of Macapá (646) and a higher incidence in Serra do Navio (26.55). Most of the notifications occurred in the age group of 20 to 29 years (47.7%), the brown race (74.75%), pregnant women with incomplete middle school (22.21%), housewives (58.82%), third trimester of pregnancy (50.71%) and the classification of the disease in the primary phase (27.28%). The prevailing treatment was benzathine Penicillin G 7,200,000 IU (49.39%). The findings indicated an annual increase in syphilis notifications during pregnancy, as well as considerable growth in the annual incidence coefficient in the counties of the State of Amapá, revealing the need to interrupt the syphilis transmission chain.